HUBUNGAN KEPATUHAN MINUM OBAT DAN DUKUNGAN KELUARGA DENGAN KESEMBUHAN PENDERITA SKIZOFRENIA - Suyatni Musrah, Andi; Nugroho, Hadi; Yulidar, Elfina; Azfari Azis, Waode; Taswin, Taswin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Schizophrenia is a group of psychotic disorders, with basic personality disorders, characteristic distortions of thought processes. These disorders are generally characterized by distinctive, erroneous thoughts and perceptions, as well as dulled affect, the exact cause of Schizophrenia is not yet known. However, Schizophrenia can be experienced by a person due to several factors. Some therapies to cure schizophrenia include biological therapy and psychosocial therapy. One of the main factors for the success of medical therapy in schizophrenia patients is the continuity of treatment in the management of schizophrenia and family support. Patients who are not compliant with treatment will have a higher risk of relapse compared to patients who are compliant with treatment. This study used an analytic design with a cross sectional design. The analysis used was frequency distribution and Chi Square test. The results of this study concluded that there was a relationship between adherence to taking medication (p value 0.000; = 0.05), family support (p value 0.001; = 0.05) with the recovery of schizophrenia patients in the psychiatric clinic of Riau Province Mental Hospital. Suggestions from this study are expected for respondents and families to be able to add insight into adherence to taking medication and family support to the healing of schizophrenia.Keywords: Family Support, Medication Compliance, Schizophrenia